The effect of physical activity intervention on blood pressure in 18 low and middle-income countries: a systematic review and meta-analysis of randomized controlled trials - Vahid Monfared; Mohtaram Hashemi; Fatemeh Kiani; Reyhane Javid; Mahsa Yousefi; Mahdis Hasani; Ali Jafari; Mohammad Ali Vakili; Motahareh Hasani (BMC, 2024)
Abstract Background In especially, low and middle-income nations (LMICs), where healthcare access may be restricted, high blood pressure (BP) is a major risk factor for cardiovascular disease and stroke, both of which can even lead to death. Altering one's lifestyle, in conjunction with medical therapy, has been demonstrated to be effective in lowering BP. Recent research has shown that physical activity (PA), in a variety of guises and to varying degrees, can be an effective means of lowering BP. Objective The purpose of this meta-analysis and systematic review was to evaluate the impact that PA plays in the development of hypertension in LMICs nations. Methods An exhaustive search of the available research was carried out in order to locate studies that were pertinent. We searched a number of online databases, such as SCOPUS, Medline, and Web of Science, looking for clinical trials that were published before March of 2023. Studies were only considered for inclusion if they were randomized controlled trials (RCTs), reported on the association between PA and BP, and were carried out in LMICs countries. Results This meta-analysis incorporated a comprehensive collection of 60 studies, encompassing a total of 11,002 people, consisting of 5,630 cases and 5372 controls. The findings indicate that engaging in PA had a notable impact on decreasing systolic blood pressure (SBP), as seen by a weighted mean difference (WMD) of -7.70 mmHg, with a 95% confidence interval (CI) ranging from -9.50 to -5.91 (p < 0.001). Additionally, PA was found to have a significant influence on reducing diastolic blood pressure (DBP), as indicated by a WMD of -3.60 mmHg, with a 95% CI ranging from -4.48to -2.73(p < 0.001). The findings from subgroup analysis indicate that the observed results remained statistically significant when considering individuals with baseline SBP of 120 mmHg or lower and DBP of 80 mmHg or lower. Conclusion The incorporation of PA can significantly contribute to the mitigation of high BP within LMICs nations. Additional investigation is required to ascertain the most effective form and amount of PA in order to mitigate BP levels within these specific individuals. Graphical Abstract